STRATEGI BERTUTUR DALAM TUTURAN MEMERINTAH PADA SITUASI KOMEDI TUKANG OJEK PENGKOLAN (TOP) (Eps. 9) - prapti wigati purwaningrum (LPPM Universitas Bina Sarana Informatika, 2017)
AbstrakThis tendency draws interest to find politeness strategy in command. This paper is using dialog script of tukang ojek pengkolan (TOP) written by Sokat Rahman. In this analysis the writer uses speech act theory by Searl, pragmatic theory by Austin, and politeness strategy by Brown C. Levinson. Based on the analysisthe writer found some commands which uttered by pilteness strategy off record and bald record. Some charecters in this serial comedy series Tukang Ojek Pengkolan preferred off record to bald record in their commands. By using this strategy, the characters uttered indirectly or vaguely to the hearer. In this strategy, the speaker tried to avoid the direct FTA, and it removes the characters from the potensial of being imposing. Keywords: Pragmatic, speech act, politeness strategy, Tukang Ojek Pengkolan (TOP) cpt.9